Microscopic Observation of π Spin Polarization by d Localized Spin in λ Type BETS Based Organic Superconductors - Hiraki, Ko-ichi; Takahashi, Toshihiro; Akiba, Hiroshi; Nishio, Yutaka; Zhou, Biao (Crystals (Basel), 2020)
In this study, 77Se NMR measurements were carried out to detect the π spin polarization of the organic BETS (BETS = Bis(ethylenedithio)tetraselenafulvalene) molecule of the field induced superconductor, λ-(BETS)2Fe1−xGaxCl4, which shows a superconducting transition at relatively low magnetic field compared to the non-doped λ-(BETS)2FeCl4. From the analysis of the NMR spectrum at low temperature, it was clarified that the exchange interaction between π and 3d spins in the Ga doping system is smaller than that in the Fe salt. It is also clarified that the conduction π spins feel the “averaged” exchange field from the localized 3d spins at the dilute Fe sites.